O bom governo de México e Michoacán: Vasco de Quiroga e a colonização utópica da Nova Espanha (1531-1565) - Witeze Junior, Geraldo (2016)
This thesis presents the work of Vasco de Quiroga and discusses his utopian project for the colonization of New Spain. It begins with a historiographical review, recovering the main interpretative lines developed over the last century; then addresses the subjects involved in quiroguian project, namely, the Spanish settlers and the Native Americans; then comes the topics that lead to utopia: just war, slavery and evangelization; finally, examines the references to Utopia to elucidate how the Quiroga understood this book and tried to apply it among the Indians, in order to build a renewed church from that new man found in America. The focus is on a careful analysis of the texts, putting the reader in direct contact with the sources, which is very different from the usual historiography. It also highlights the Utopia of Thomas More as the main inspiration through a thorough comparison between the morian text and Quiroga’s writings. Other influences are also highlighted, such as the Bible and the Philosophia Christi of Erasmus. Anyway, it aims to show the importance of knowing Vasco de Quiroga to understand the polyphonic movement of America's colonization and the development of utopian thinking as a key to the constitution of modernity. It presents a critical view of the simplistic interpretations that have created a historiographical common sense, showing that the colonial sources still has much to reveal.